Antenas de múltiple haz conmutado - Ferrando Bataller, Miguel; Valero Nogueira, Alejandro; Suárez Fajardo, Carlos Arturo; Rincón Reyes, Diego Yecid (Ingeniería, 2003)
This article gives special attention to synthesize the appropriate pattern and to propose the passive beamforming networks with N input ports, which allows to simultaneously generating one beam for each input with requirements such as low side lobe,high gain, crossover level and orthogonality condition. This multiple beam system could be a candidate for base-station demands in wireless communication services.